LIFELONG LEARNING MANAGEMENT FOR ENGINEERING SPECIALISTS IN CONTEXT OF INDUSTRY 4.0 (Development Service Industry Management, 2025)
The issues of lifelong learning are relevant in the current context of educational development in Ukraine. The paper indicates a meaningful content of such concepts as "lifelong learning", "continuing vocational education and training" and "adult education" formed during the development of the European discourse in the field of vocational education and training but has a definite difference.  It is noted that the concept of 'lifelong learning' allows the professional to build an educational trajectory that fully corresponds to their professional and educational abilities and needs. The issues of lifelong learning for engineering specialists in the context of Industry 4.0 are of great importance. The transition to Industry 4.0 requires engineers to continuously improve their knowledge and skills due to rapid technological changes.  The authors of this article developed and proposed a theory-practice IDEFØ model of lifelong learning for engineering specialists based on the Structured Analysis and Design Technique (SADT). The model provides a visual description of lifelong learning processes and aims to increase their efficiency in organizations.
Keywords: lifelong learning; engineering specialists; Industry 4.0; Structured Analysis and Design Technique (SADT); IDEFØ model